Auditing social networks on post-purchase behaviour: analysis of the content of the mentions on AliExpress in Brazil. (1st March 2020) - Laruccia, Mauro Maia; Cusciano, Dalton Tria
This study aims to study the auditing social networks in post-purchase in the mentions of customers presented on the internet. The research problem was: how can post-consumer behaviour influence marketing strategies on social media? The Scup tool used as a data collection procedure for surveying social media mentions about AliExpress in Brazil. As a result, after applying the filter described in the procedures, we obtained 71 records (N = 71) collected in the period from 29 October 2015, to 4 November 2015, reflecting the behaviour of the consumer about the post-purchase process. The result of the popularisation of social networks has changed the relationship between companies and their publics. In the past those relations was processed through official customer service channels, today is via social networks, where customers expose their opinions about product or service purchased by a particular company. Retailers as AliExpress need to improve customer experience throw social media in Brazil.